GANGGUAN BAHASA PADA ANAK USIA 7 TAHUN PENDERITA APRAKSIA LISAN - Karnadi, Mita Carina; Pertiwi, Dora Hatika; Putra, Dona Aji Karunia (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the forms of phonological disorders and the causes of language disorders in children aged 7 years with oral apraxia. This study used descriptive qualitative method. Qualitative descriptive is used to analyze and develop data that researchers get from research sites. The subject of this study was a 7 years old child who suffered from oral apraxia with the initials NP. The research data is in the form of speech between the subject and the speech partner. The techniques used are interviews, observations, listening, and notes. The theory used is the theory of phonology and syllables. The results of the study showed that children aged 7 years with oral apraxia experienced some form of cognitive phonological disturbance, namely phoneme pronunciation disorders in the form of phoneme deletion and phoneme changes. Researchers also found factors that cause language disorders in children with verbal apraxia, namely internal factors and external factors.